Overcoming Primary Cervical Dystocia with Ayurveda Therapeutic Strategy- Case Study (International Journal of Ayurveda and Pharma Research, 2022)
Background: We report a case of primary cervical dystocia managed successfully with Ayurveda therapy. The classical Ayurveda lexicons comprise detailed descriptions regarding Prasava (labor) and its management based on which the present case was intervened which resulted in achieving progressive improvement in cervical dilatation and achieving normal labor.Case Presentation: The case reported in this study is primigravidae, 25 years’ old visited prasutitantra OPD, NIA hospital with 37.2 weeks gestational age complaining of labor pains. Since her contraction and per vaginal findings were suggestive of onset of labor, she was hospitalized for further monitoring and awaited spontaneous progress of labor. Repeated Per vaginal examination revealed no progress in cervical dilatation even after 28 hours and she was diagnosed with primary cervical dystocia. Intervention of Kebuka taila yonipichu-25ml 2 hourly was made which resulted in remarkable cervical dilatation equivalent to mean standard rate following 3 interventions of yonipichu within 6 hours.Conclusion: The status of the cervix during labor is a significant determinant of mode and ease of labor. Ayurveda therapeutic strategy of Kebuka taila yoni-pichu can effectively prime the cervix due to the Garbhashayaka sankochaka and estrogenic properties of Kebuka and the activation of Ferguson's reflex by Yoni-pichu.